Tingkat Kemampuan Netting dan Backhand pada Atlet Usia 9-14 Tahun di PB TalentaKabupaten Kebumen - AZIS SAPUTRA, YUZA FATHUDIN; Raharjo, Agus (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the ability level of netting and backhand strokes in Pb athletes aged 9-14 years. Talents. This study uses a quantitative approach with descriptive results. Using a survey method with data collection techniques using tests and measurements. The instrument is a test of the ability to hit the netting and backhand. Then the analysis is poured in the form of a percentage. The results show that in the "very poor" netting category, 3.3% totaled 1 athlete, "less" 30%, 9 athletes, 11 athletes, 36.7% with "enough" abilities, 23.3% athletes with "good" abilities. ” with a total of 7 athletes and 2 athletes with a percentage of 6.7% with very good abilities. and athletes with very poor backhand ability by 10% totaling 3 athletes, lacking ability by 16.7% with a total of 5 athletes, 30% of athletes with sufficient ability with a total of 11 athletes, 43.3% athletes with a total of 13 hitting abilities athlete. The conclusions in the research on the level of ability in netting and backhand strokes in Pb athletes. Kebumen talents aged 9-14 years get the category of “adequate” netting and “good” backhand. However, there is a need for increased training and programs to develop basic netting and backhand techniques.